A Representation Model of Design Rationale for the Design of ERP System - Kawamoto, Sandra; Almeida Junior, Jorge Rady de (INFOCOMP Journal of Computer Science, 2009)
Special attention has been given to documentation and support activities in Software Engineering design, mainly when they are related to complex systems and distributed teams. Usually, information related to the final decisions of each phase is registered. However, the reasons of each decision and the alternatives that were considered and discarded are not documented. Capture and recovery of this type of information, in an efficient way, are the purposes of the Design Rationale study. Recording this information can facilitate maintenance, reuse and even the design phase, providing a better understanding of the system, by knowledge spread, communication and integration among the project team. The main concern is when and how to capture this information with low interference in designers’ usual activities, so that benefits can overcome the costs involved in this task. The purpose of the present work is to show, with plausible reasons, the great usefulness of the application of the Design Rationale technique in ERP systems design, proposing a new representation model for recording design decisions in these systems.